ГИДРОЛОГО-МОРФОДИНАМИЧЕСКИЙ АНАЛИЗ СВОБОДНО МЕАНДРИРУЮЩИХ РУСЕЛ НА РАЗНЫХ СТАДИЯХ РАЗВИТИЯ - Баровский Н.А. (My University, 2005)
The evaluation is given to longitudinal and transversal displacements of free meanders at the different stages of evolution and on conditions of different flow of river and flood plain's height. The expressions for the velocity of meandering channel displacement in relation to multiannual flow changes were obtained for different stages of evolution. The length and location of washout front of concave bank of meander correlates with multiannual flow changes.
Keywords: 551.435.11